Hierarchical Synthesis, Structure, and Photophysical Properties of Gallium- and Ruthenium-Porphyrins with Axially Bonded Azo Ligands - Gao, Yueze; Walter, Vroni; Ferguson, Michael J.; Tykwinski, Rik R. (Chemistry - A European Journal, 2020)
The hierarchical synthesis of three porphyrin and four bisporphyrin derivatives is presented. This strategy relies on the incorporation of linkers based on azo moieties appended with pyridyl and/or acetylenic groups that facilitate axial coordination to Ga- and Ru-metalloporphyrins. These porphyrinic systems allow for a quantitative analysis of the effects of diamagnetic anisotropy (DA) by using H-1 NMR spectroscopic and X-ray crystallographic analyses. A simple power-law relationship between the proton chemical shift and the distance from the porphyrin core is experimentally outlined, which confirms previous theoretical predictions and shows that the limit of DA is about 2 nm. Photophysical properties of the azo-linked porphyrins are analyzed by UV/Vis spectroscopy, showing that significant cis-trans isomerization is not observed for azo ligands bound only to Ga-porphyrins. Incorporation of Ru-porphyrins to an azo ligand facilitates photoswitching behavior, but the process faces competition from decarbonylation of the Ru-porphyrin, and appreciable switching is only documented for GaL1Ru.
CRIS-Team WoS Importer:2020-11-20